2011
DOI: 10.4103/0972-0707.82606
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-made endodontic obturator for the management of Blunderbuss canal

Abstract: The complex anatomy of the blunderbuss root canal often poses a major challenge to accomplish adequate obturation for a biological seal. Moreover, the roll-cone, Gutta-percha obturation technique, which is routinely practiced, also results in a mismatch and failure to configure to the canal volume in the absence of an apical barrier. Hence, an attempt has been made to tailor-make a heat polymerized polymethyl methacrylate resin as an endodontic obturator, to match the canal volume, which has been ascertained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[15] Now we can calibrate the diameter of open apex in cubic millimeter by CBCT (cone beam computed tomography), Spiral CT (computed tomography), and Ultrasound also confirmed the nature of the periapical tissues. [16] Novel bio regenerative and highly biocompatible material like MTA (calcium silicate) based single-visit apexification can be a better option for open apex cases to achieve a higher success rate in today's scenario. This case report suggested that MTA based one visit apexification with walking bleach is the best conservative procedure of choice which restores the esthetic of the natural tooth for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Now we can calibrate the diameter of open apex in cubic millimeter by CBCT (cone beam computed tomography), Spiral CT (computed tomography), and Ultrasound also confirmed the nature of the periapical tissues. [16] Novel bio regenerative and highly biocompatible material like MTA (calcium silicate) based single-visit apexification can be a better option for open apex cases to achieve a higher success rate in today's scenario. This case report suggested that MTA based one visit apexification with walking bleach is the best conservative procedure of choice which restores the esthetic of the natural tooth for the patient.…”
Section: Discussionmentioning
confidence: 99%